The “Big Three” in biocompatibility testing of medical devices: implementation of alternatives to animal experimentation—are we there yet? - Kanďárová, Helena; Pôbiš, Peter (Frontiers in Toxicology, 2024)
Biocompatibility testing ensures the safety of medical devices by assessing their compatibility with biological systems and their potential to cause harm or adverse reactions. Thus, it is a critical part of the overall safety evaluation process for medical devices. Three primary types of biocompatibility tests—cytotoxicity, irritation, and sensitisation assessment—are standard for nearly all medical devices. However, additional biocompatibility tests, such as genotoxicity, systemic toxicity, hemocompatibility, and implantation studies, may also be necessary, depending on the device’s nature and intended use. The testing is partly conducted in vitro, but the industry still heavily relies on animal experiments. Compared to other industrial sectors, implementing alternatives in medical device biocompatibility testing has been notably slower. This delay can be attributed to the absence of specific validation processes tailored to medical devices and the resulting hesitation regarding the predictive capacity of these alternative methods despite their successful applications in other domains. This review focuses on the progress and obstacles to implementing new approach methodologies in the areas of cytotoxicity, irritation and sensitisation testing of medical devices. While challenges persist in adopting these innovative methods, the trend towards embracing alternatives remains robust. This trend is driven by technological advancements, ethical considerations, and growing industrial interest and support, all collectively contributing to advancing safer and more effective medical devices.